SISTEM INFORMASI MANAJEMEN EKSTRAKURIKULER BERBASIS WEBSITE PADA SMA NEGERI 16 JAKARTA - Rini Nurhasanah (2022)
SMA Negeri 16 Jakarta is one of the schools that provides extracurricular activities for its students. The extracurricular process from registration to assessment is still conservative. This results in an inefficient process both in terms of cost and time used. Therefore, this study aims to build a system that can facilitate students in obtaining information about extracurricular activities and facilitate the school in processing data on extracurricular activities. This information system is built by utilizing the PHP programming language which is supported by the Laravel framework and MySQL. This research applies UML to design the system and the waterfall method as a software development method. The results obtained in this study, namely a website-based extracurricular management information system that makes it easy for students to obtain information related to extracurriculars, makes it easier for students to register extracurriculars online, and assists the school in digitally processing data.